Wijhāt an-Naḍar ad-Dīniyah wa aṡ-Ṡaqāfiyah fī Riwāyati “Banāt ar-Riyāḍ” li Rajaa al-Sanea: Naqd Adabī Islāmī: وجهات النظر الدينية والثقافية في رواية "بنات الرياض" لرجاء الصانع: نقد أدبي إسلامي - Tatik Mariyatut Tasnimah; Husain Miftahul Rizqi; Ghazali bin Zainuddin (LISANIA: Journal of Arabic Education and Literature, 2024)
This study aims to analyze the religious and cultural views of Rajaa al-Sanea in her novel Banāt Riyad from the perspective of Islamic literature. The novel has garnered both support and rejection from readers since its publication in 2005. The author portrays the characters with a lifestyle like American girls. Not only is the figure's name Westernized, but even the way of dressing and appearance is also very different from the habits of Saudi girls. However, the novelist claims that religious superiority exists in her novel. This research is qualitative. The data collection technique in this study is a documentation technique. This study uses the method of literary criticism from the perspective of Islamic Literature، which paralleles the mission of literary works and Islamic teachings. The criteria for judging and criticizing Islamic literature for works of fiction prioritize noble values and propriety, not freedom of expression. Based on this perspective، the researcher identifies deviations from Islamic teachings contained in the novel. The behavior of the novelists does not reflect the image of Islam. Harassment of religious symbols appears in the dialogue of characters who often use vulgar language. Gentle, beautiful, and polite language is not found in this novel.